Rutinas alimenticias en el hogar y el desperdicio de alimentos - Casimiro Rodriguez, Elizabeth Jazmin (2020)
Reducing food waste in the world is one of the greatest challenges towards a sustainable world. One third of the food produced around the globe is being thrown away. A household plays an important stage of food collection, and coincidentally, it is where most food is wasted. This study examines the determinants of food waste, based on the Theory of Social Practice, focusing on the approach of eating routines at home. A total of 383 persons from Metropolitan Lima were surveyed about their most common sociodemographic characteristics and their routines of planning, buying, storing and reusing food. The results show that the routines of buying, cooking and reusing food are the major determinants of food waste for the sample studied. In addition, the number of members and children in the household are important factors regarding the generation of waste. Finally, the possibilities are open for private and public companies to guide policies and social marketing actions for more responsible practices